Pulmonary echinococcosis mimicking tuberculosis in a child from a dual-endemic region: a case report - Li, Yiyuan; Liu, Yang; Guo, Qin (Frontiers in Pediatrics, 2025)
BackgroundPulmonary echinococcosis represents a significant health challenge, particularly in endemic regions, and is associated with substantial morbidity and mortality. Its nonspecific clinical presentation and radiological diversity often lead to misdiagnosis. Here, we report a case of pulmonary echinococcosis initially misdiagnosed as pulmonary tuberculosis.Case presentationWe report a case of a 13-year-old girl from a region endemic for both echinococcosis and tuberculosis. She initially presented with recurrent cough, hemoptysis, night sweats, and a pulmonary cystic lesion and was diagnosed with pulmonary tuberculosis. However, her condition progressively deteriorated despite antituberculosis therapy. Ultimately, surgical intervention and histopathological examination confirmed pulmonary echinococcosis, and the patient achieved complete recovery after therapy.ConclusionFor patients from regions endemic for both tuberculosis and echinococcosis who present with cough, hemoptysis, or pulmonary cystic or cavitary lesions, it is crucial to differentiate pulmonary echinococcosis from pulmonary tuberculosis. The final diagnosis should be supported by other microbiological-serological and/or histopathological tests.